2017
DOI: 10.1371/journal.pone.0173153
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical model of bacterial interactions in two-species oral biofilms

Abstract: Periodontitis are bacterial inflammatory diseases, where the bacterial biofilms present on the tooth-supporting tissues switch from a healthy state towards a pathogenic state. Among bacterial species involved in the disease, Porphyromonas gingivalis has been shown to induce dysbiosis, and to induce virulence of otherwise healthy bacteria like Streptococcus gordonii. During biofilm development, primary colonizers such as S. gordonii first attach to the surface and allow the subsequent adhesion of periodontal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…It can be found that all models reach the maximum concentration after about 30 days (Figure 2b) and all models show higher concentration for nitrite oxidizer (Figure 2(c)). Hereafter we selected double Monod kinetics due to its better numerical behavior during simulations, besides it was more commonly used in previous studies …”
Section: Solution Strategy and Validationmentioning
confidence: 99%
“…It can be found that all models reach the maximum concentration after about 30 days (Figure 2b) and all models show higher concentration for nitrite oxidizer (Figure 2(c)). Hereafter we selected double Monod kinetics due to its better numerical behavior during simulations, besides it was more commonly used in previous studies …”
Section: Solution Strategy and Validationmentioning
confidence: 99%
“…It is therefore mixed-species biofilms that are mostly apparent in situ, and thus the study of inter-species interactions within a biofilm is of great importance in addressing the challenges associated with biofilm control. Studying the role of mixed species interactions on biofilm growth is experimentally challenging [44] and mathematical models can be of great help [44,46,60]. In particular, we describe two recent applications of mathematical models which reveal key mechanisms in biofilm communities involving multiple species.…”
Section: Mixed Species Interactionsmentioning
confidence: 99%
“…Recently, a new 2D cellular automata (discrete space and time) model has been developed to study biofilm formation of two species of bacteria, Streptococcus gordonii and Porphyromonas gingivalis [44]. These two species have been identified as the leading causes of periodontitis, commonly referred to as gum infection, which can lead to tooth loss around the infected area.…”
Section: Mixed Species Interactionsmentioning
confidence: 99%
“…La procédure adoptée pour l'étude des interactions entre S. gordonii et P. gingivalis a consisté en 2 grandes étapes (Figure 2A et B [5]. La croissance des bactéries en biofilm est modélisée au moyen d'un automate cellulaire à 2 dimensions (largeur x hauteur) dans lequel chaque bactérie est considérée comme un individu caractérisé par un comportement qui lui est propre (Figure 1) [6].…”
Section: Simulation Mathématique Des Interactions Bactériennes Inter-unclassified